Desain Alat Ukur Regangan Menggunakan Strain Gauge Berbasis Arduino Uno - Susanto, Herdi; Husen, Zakir; Marbun, Mahmuddin; Hanif, Hanif; Mawardi, Mawardi; Hasdi, Syaiful; Ichwan, Hasbi Randi (universitas teuku umar, 2025)
Industrial applications, machinery and engineering construction, strain is the most important value for determining the selection of suitable and appropriate materials for designing machine elements, with advances in strain measurement analysis technology on Arduino microcontroller-based structures it is very possible to use it. Several studies have succeeded in measuring strain using an Arduino Uno-based strain gauge. Based on the above, it is possible to design a strain measuring tool using an Arduino Uno-based strain gauge to support students' practicum process, so in this research a design of a strain measuring tool using an Arduino Uno-based strain gauge was carried out. The research results have completed the design of a strain measuring tool using an Arduino Uno based strain gauge and can be used on a student practicum scale. The results of tests carried out on Nako iron rods show that there is an appropriate relationship between the load applied, the strain measured and the stress produced. The results of the tests carried out measured the amount of strain produced at various loads such as at a load of 1,000 grams the strain was measured at 0.5345 and a stress of 106.9 MPa. Meanwhile, at a load of 2,000 grams, the strain reached 0.573 and the stress was 114.6 Mpa.